Síntese de nanopartículas de óxido de ferro obtidas pelos métodos de termólise e micro-ondas para aplicação em hipertermia magnética - FONSECA , Renilma de Sousa Pinheiro (2019)
Iron oxide nanoparticles are materials that exhibit superparamagnetic behavior due to monodomain formation due to particle size reduction. When subjected to an alternating magnetic field such as nanoparticles, it releases heat energy to the adjacent system. Among the applications susceptible to these structures is a magnetic hyperthermia, which consists in the elevation of body temperature, promoting the adoption of neoplastic cells. In this context, the present work deals with the study of the exposure parameters of Fe3O4 magnetite nanoparticles, the thermolysis method and the microwave assisted solvathermic method, which are recovered with gold for the core@shell tests of the type Fe3O4@Au for application in magnetic hyperthermia. Therefore, it can be considered contribution of additives involved in temperature (oxidation oxidation temperature, metallic precursor, solvent, reaction time and strong reducing agent), having as objective or control the phase composition and size of nanoparticles, besides understand the role of each additive and possible inherent changes thereto under the crystal structure. The study of the terminology method indicates the formation of Fe3O4 using FeCl3 from the application of oxidation temperature, but with unused sample addition. In contrast, iron tris-acetylacetonate III shows single-phase Fe3O4 formation within the nanometer scale with application of 1-octadecene as solvent, 2-hour reaction and 1-dodecanol as reducing agent. A nanoparticle heat generation analysis demonstrates SAR equal to the next 27 W.g-1, validating a magnetic hyperthermia application.The use of the microwave solvent assisted method enables the formation of Fe3O4 with a power of 1500 W, a temperature of 240 °C and a reaction time equivalent to 30 minutes. In both synthesis methods, surfactant materials, oleic acid and oleilamine, chemotherapeutic agents on a nanoparticle surface by FTIR and RAMAN analysis, as well as classical statistics of superparamagnetic and nanoscale materials, corroborated by the XRD, TME analysis. and VSM. The captured materials were transferred to aqueous medium and later recovered with gold, characterized by UV-vis and VSM, including Fe3O4@type structures training on the nanometer scale. A cytotoxicity assessment for gold-free nanoparticles indicates low toxicity in normal cells and selectivity for neoplastic cells, MCF-7 and HeLa, characterizing the potentiality for application in biological systems.